Viral food culture and social identity: A phenomenological study of Gen Z - Siti Salwa Az’zahra; Jundi Nabil Nazhmi; Rima Asyiah; Ardelia Putri Pratama Hidayat; Fauzan Ahdi Widyaputra (Privietlab, 2026)
The rapid growth of viral culinary trends on social media, particularly TikTok and Instagram, has shaped new consumption patterns among Generation Z in Indonesia, often driven by the Fear of Missing Out (FOMO) (Przybylski et al., 2013). This study explores how Generation Z social media users subjectively experience and interpret viral food trends through Schutz’s (1967) phenomenology of the life-world, with explicit attention to informants’ stock of knowledge, intersubjectivity, and the because-motives and in-order-to-motives that underlie their participation. Using a qualitative phenomenological design grounded in Schutz’s (1967) framework, four Gen Z informants were selected through purposive sampling, and the interviews showed sufficient thematic adequacy for exploratory phenomenological analysis. Data were collected through in-depth semi-structured interviews and digital trace analysis, and analyzed through a Schutzian thematic procedure moving from descriptive coding to eidetic (essence-focused) interpretation. The findings show that TikTok’s algorithmic curation functions as a shared, intersubjective stock of knowledge that continuously exposes informants to viral food content, generating sensory curiosity prior to actual consumption. FOMO operates as a because-motive rooted in informants’ prior experiences of social exclusion, while their in-order-to-motives are oriented toward maintaining social belonging and digital relevance. Viral food consumption thus functions simultaneously as consumption, communication, and identity performance, producing both positive (culinary exploration, social bonding, support for small businesses) and negative (impulsive consumption, unmet expectations) outcomes. This study contributes to communication and consumption studies by offering an explicitly Schutzian account of subjective meaning-making in digital food culture and by underscoring the need for critical digital consumption literacy among Generation Z.